Seizure disorders in pregnancy: an insight beyond eclampsia and epilepsy - Sharma, Arti; Gupta, Vineeta; Sarda, Prashant; Singh, Parul; Gupta, Nikita; Kohli, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Seizures in pregnancy contribute to poor maternal and perinatal outcome. Though eclampsia and epilepsy are common causes of seizures in pregnancy but there are several other conditions apart from eclampsia and epilepsy which give rise to convulsions. Objective of this study was to evaluate fetomaternal outcome in patients with seizure disorders as well as to analyze the other causes of seizures in pregnancy apart from eclampsia and epilepsy. Methods: This prospective study was conducted in Shri. Guru Ram Rai institute of medical and health sciences, Dehradun, India over a period of 39 months from January 2017to March 2020, in all pregnant women with seizure disorders delivered in this hospital. In all cases demographic characteristics, causes of seizure with special attention on noneclamptic, non-epileptic conditions, maternal complications, mode of delivery and fetal outcome were noted. Results: Total 97 cases with seizure disorders were included in the study. Mostly seizures were due to eclampsia and epilepsy in 91.75% cases. Among other causes neurocysticercosis, cerebral malformation, posterior reversible encephalopathy syndrome, brain tumor, and cerebral infarcts contributed to seizures in pregnancy in 8.25%cases. Maternal complications were premature rupture of membranes, gestational diabetes mellitus, hypothyroidism, anaemia, jaundice and abruption observed in37.11% cases. Live birth rate was 76.28%, prematurity was present in 27.83% cases and fetal growth restriction was seen in 7.21% neonates. There were 5 (5.15 %) neonatal deaths. Conclusions: Seizure disorders in pregnancy are associated with significant increase in maternal and fetal risk. Maternal complications, cesarean section rate and neonatal complications are increased. Several other conditions apart from eclampsia, need to be considered in patients without epilepsy presenting with convulsions in pregnancy.